Risk management, expectations and global finance: The case of Deutsche Bank 1970-1990 - Alexander Nützenadel (Humboldt University Berlin, 2022)
What impact do past experiences have on the expectation formation of banks? This article analyses the risk management of Germany's largest bank during the 1970 and 1980s. In this period, financial deregulation and globalization increased the likelihood of credit defaults and forced banks to implement new strategies of risk assessment. The Herstatt failure of 1974 triggered a series of new regulations, partly based on initiatives of the banks themselves. After the sovereign debt crisis of the 1980s, banks introduced a comprehensive strategy of country-risk assessment. They systematically professionalized their information resources and integrated risk and liability management. Economic forecasting was often based on historical data used for the classification and diversification of risks. However, learning from past experiences had limitations, as recent events were often overrated. This had the effect that the banks' country risk assessment focused mainly on developing countries while the industrial world was not included in the schemes. This might explain why many banks have continually underestimated the financial risks present in developed countries since the 1990s.
urn:nbn:de:kobv:11-110-18452/26265-8
Keywords: F65; G15; G17; G32; N2; 330; Risk management; financial markets; banks; expectations; historical experience